Bridging Scales and Knowledge Systems: Concepts and Applications in Ecosystem Assessment - V.Reid Walter (MC Graw Hill, 2006)
Bridging the gap between local knowledge and western science is essential to understanding the world's ecosystems and the ways in which humans interact with and shape those ecosystems. This book brings together a group of world-class scientists in an unprecedented effort to build a formal framework for linking local and indigenous knowledge with the global scientific enterprise. Contributors explore the challenges, costs, and benefits of bridging scales and knowledge systems in assessment processes and in resource management. Case studies look at a variety of efforts to bridge scales, providing important lessons concerning what has worked, what has not, and the costs and benefits associated with those efforts. Drawing on the groundbreaking work of the Millennium Eco-system Assessment, "Bridging Scales and Knowledge Systems" will be indispensable for future efforts to conduct ecosystem assessments around the world.